Ungauged flood modelling for Kuantan River Basin using HEC-HMS - Mohd Hisyam, Zulkifli (2018)
Floods in the monsoon season not only affect urban catchment areas, also affect rural areas. Therefore, a study should be conducted to avoid the crisis of damage caused by floods in rural areas. All sub-basins in the Kuantan River Basin majority do not have river flow data. Only one station available to records river flow data, which is Bukit Kenau station. Therefore, a study to predict rainfall-runoff of Sungai Kuantan using the Hydrologic Engineering Center-Hydrologic Modeling System (HEC-HMS) was selected to simulate the river flow for ungauged catchment. Runoff is very important in flood studies as it characterizes river flow. The Hydrologic Engineering Center-Hydrologic Modeling System (HEC-HMS) has been chosen for the simulate as considered the best source of water resources and the easiest method to analyze and predict the flow of rain-water of the Kuantan River. The purpose of this study is to predict the flow of river water for a sub-basin that does not have a river water flow record. The Clark method was used for the entire Kuantan River Basin. This method is used to stimulate river basin flow. Therefore, rainfall data is obtained from the Drainage Department, from 1970 until 2015. The data used are rain data. The data were obtained using four (4) rain events of 1 hour, 6 hours, 24 hours and 72 hours rainfall duration with three (3) different ARI which are 2-years ARI, 10-years ARI and 100-years ARI. The SCS Curve Number in HEC-HMS is used to determine the loss of water caused by infiltration. Based on the result obtained, the highest river flow occurs in Belat sub-basin and the lowest river flows occur in the sub-basin of Sungai Isap. This is due to the largest area of rain catchment for Belat sub-basin and the smallest rain catchment area for Sungai Isap sub-basin.